History of Hajj Pilgrimage in Colonial South Asia: An Analytical Review of Rishad Choudhury’s Hajj across Empires - Muhammed Sufyan Vv (Penerbit Hellow Pustaka, 2025)
The Hajj pilgrimage has historically served as more than a religious obligation; it has functioned as a conduit of transregional exchange and political imagination across the Muslim world. Rishad Choudhury’s Hajj across Empires: Pilgrimage and Political Culture after the Mughals, 1739-1857 explains on this dynamic in the context of South Asia, specifically in the period after the fall of the Mughal Empire and during the rise of British colonialism. The book is a prominent contribution to Islamic, South Asian, and transimperial history, providing an exact account of how pilgrimage intersected with politics, identity, and empire. Choudhury traces how the Hajj functioned not only as a spiritual journey but also as a political and cultural encounter in the age of empire. Through a comparative lens, the book highlights the ways in which South Asian Muslims navigated the shifting dynamics of British and Ottoman imperial politics, as well as local social transformations, during the nineteenth and early twentieth centuries. The study emphasizes the importance of viewing pilgrimage not merely as a religious duty but as a complex, historically contingent phenomenon shaped by broader geopolitical forces. A particular focus of this study is the tragic incident at Ezhimala during the colonial period, where a Hajj-bound ship was set ablaze, resulting in the loss of numerous pilgrims’ lives. This event, though often overlooked in broader narratives, serves as a poignant example of the vulnerabilities faced by pilgrims in a politically charged and racially stratified colonial maritime world. By analyzing this episode within the framework of Choudhury’s trans-imperial perspective, the paper explains on the perils of religious mobility under colonial surveillance and highlights the localized tensions that mirrored the broader imperial contestations surrounding the Hajj.